THE STRUCTURE OF AN ENTOMOFAUNA CHARACTERISTIC FOR A SPONTANEOUS MEADOW IN SIBIEL VILLAGE (SIBIU, ROMANIA) - Cristina STANCĂ-MOISE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper complements previous studies characterizing the useful and harmful insect species existing in different types of ecosystems in the village of Sibiel (Sibiu). The study presents quantitative relations resulted from the ecological typology established by observations and research. Research related to the application of the information theory in knowledge of the biota structure of a grassland ecosystem, with quantities and qualitative ratios related to useful and harmful fauna for the studied meadow have not taken any further. The present study is a beginning knowledge of entomofauna specific for spontaneous grasslands, providing useful data for those interested in setting a system of integrated pest control in these biotas.